Response from Kalra S, Arora S, Kapoor N. (J Pak Med Assoc. 2023;73:1544-5) Use of Dairy Products in People Living with Diabetes - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
Madam, We thank Kumar PP1 for their insightful comments on the paper titled Use of Dairy Products in people living with diabetes.2 Dairy products are a heterogenous group of food stuffs, as mentioned by Kumar et al. Person- centred diabetes care expects that the health care professional be aware of the variety of local dairy products, their cost, caloric and nutrient value, and seasonal availability. One should also be aware of the ways in which dairy foods can be prepared, cooked and consumed.3 The same word may have different connotations for different people. For example, buttermilk or lassi may be thick or dilute, sweetened or salted. Cheese may be processed and salted, or fresh cottage cheese and unsalted. Butter may be salted, unsalted, preserved or freshly churned from milk. Milk can be sourced from cows, buffaloes, goats, camels or other mammals, and can be consumed full cream, toned or double toned. These distinctions are important, as they impact glycemic levels and management. These subtle, and not-so-subtle differences, explain the varying findings of research on dairy products and risk of diabetes, or glycaemic control. Dairy product consumption should be viewed as part of a wider dietary landscape. Persons who take sufficient amounts of meat, chicken, fish and eggs are able to achieve adequate protein intake from these sources.4 Many people, however, do not consume these foodstuffs, because of economical, religious or cultural reasons. Milk and milk products become the main source of proteins in such individuals. Continues...